Analisis Faktor-Faktor Yang Mempengaruhi Ekspor Komoditi Teh Indonesia - Belanda - Fuja Prima Yuda; Idris Idris (Universitas Negeri Padang, 2022)
Quantitative research is a research that relies more on statistical analysis tools in this study to prove statistically that there are a number of factors that affect the volume of Indonesian commodity exports, especially to the Netherlands. This research is a kind of descriptive and inductive research. The data used are quarterly secondary data from 2010 to 20191) Commodity prices have a negative and significant effect on the volume of Indonesia's exports to the Netherlands. This finding can be interpreted when an increase in Indonesian commodity prices will encourage a decrease in the volume of Indonesian exports to the Netherlands. 2) Export tax has a negative and significant effect on the volume of Indonesian exports to the Netherlands. 3) The exchange rate has a positive effect on the volume of Indonesia's exports to the Netherlands. 4) Gross domestic product has a positive effect on the volume of Indonesia's exports to the Netherlands.